2010
DOI: 10.7763/ijesd.2010.v1.20
|View full text |Cite
|
Sign up to set email alerts
|

Study on Changes of Protein and Lipid of Fish Protein Concentrate (FPC) Produced form Kilkasin VP and MAP Packages at Light and Darknesscondition During Six Months

Abstract: Fish protein concentrate (FPC) is a healthy, sustainable and high nutritive product that sanitizedly produced from fishes in which, protein and other nutrients are more concentrated than in fresh fishes. The aim of this research is to study on the sustainability of FPC produced from kilka in two VP (Vacuum Packaging) and MAP (Modified Atmosphere Packaging) packages in light and darkness condition during six months. According to our results protein rate was 91.2%, lipid:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
3
0
3
Order By: Relevance
“…Unfortunately, a small portion of the Kilka catch is used by human (4%) due to its small size, easy deterioration, impossibility of gutting right away after catching, difficulties in hygienic preservation, packaging, and supply and the rest is used as fish meal for poultry and in aquaculture (Khoshkhoo et al. ; Khanipour et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, a small portion of the Kilka catch is used by human (4%) due to its small size, easy deterioration, impossibility of gutting right away after catching, difficulties in hygienic preservation, packaging, and supply and the rest is used as fish meal for poultry and in aquaculture (Khoshkhoo et al. ; Khanipour et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, protein concentrate produced from bream fish with a protein content of 91.63%, is FPC type A, which complies with FDA and FAO rules. In another study by Khoshkhoo et al [23] on the production of FPC from kilka fish (Clupeonella cultriventris), the protein content was reported about 0.92%. Differences in the concentrations of proteins and other chemical and physical factors may depend on the season, the species used, the production method, and other parameters [24,25] .…”
Section: Discussionmentioning
confidence: 96%
“…FAO (The Food and Agriculture Organization of the United Nations) has set 8% the maximum acceptable moisture content of FPC type A [4] . Khoshkhoo et al [23] with producing FPC from kilka fish reported the moisture content of 3.2%, and Mohamed et al [26] with producing FPC of carp and shark reported the moisture contents of 9.10 and 8.55%, respectively. Also, in the present study, by measuring the moisture content of fish patty containing FPC during 30 days of storage at ambient temperature, observed that moisture changes were not significant between control sample and treatments containing FPC in different days, but the moisture content of the samples was significant from 0 to 30 days of storage.…”
Section: Discussionmentioning
confidence: 99%
“…Protein concentrate cá (FPC) là một sản phẩm chứa chủ yếu là các mạch pepetide có phân tử lượng nhỏ, có giá trị dinh dưỡng cao, có lợi cho sức khỏe được thu nhận từ các loại cá, có thành phần các chất dinh dưỡng đặc biệt là protein cao hơn so với nguyên liệu cá tươi [1]. Theo Tổ chức Lương Nông (FAO) của Liên Hiệp Quốc [2], FPC bao gồm ba loại: (a) Loại A là bột hầu như không mùi, không vị, có hàm lượng chất béo tối đa khoảng 0,75 % và có hàm lượng protein trong khoảng 65-80 %; (b) Loại B, là bột có mùi cá và có hàm lượng chất béo tối đa là 35 %; (c) Loại C; là thịt cá được sản xuất trong điều kiện vệ sinh.…”
Section: Mở đầUunclassified
“…Thành phần amino acid của mẫu FPC Bảng 1. Thành phần 1 * amino acid thiết yếu; ** amino acid bán thiết yếu (thiết yếu trong một số trường hợp đặc biệt) 1 Các số liệu được thể hiện dưới dạng trung bình của các lần lặp lại (n=3), độ lệch chuẩn của tất cả các số liệu đều ở mức <0,5 % so với kết quả trung bình của mẫu.…”
Section: Trang 90unclassified